A Study of Management Strategies to Control Bullying at Secondary Level in Gujrat: Muhammad Shabbir, Azhar Mumtaz Saadi - Muhammad Shabbir; Azhar Mumtaz Saadi (JELM, 2020)
Innovative assessments that allow students to manipulate data and role play are currently being produced using the CBT method. But when not properly designed, students could lose their interest in adopting it.